Proceedings of the Health Science International Conference (HSIC 2017) 2017
DOI: 10.2991/hsic-17.2017.63
|View full text |Cite
|
Sign up to set email alerts
|

Support System on Successful Exclusive Breastfeeding on Primipara Based on Theory of Maternal Role Attainment

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…In this study, 50% of the respondents who received information on breastfeeding were shown to be successful in exclusive breastfeeding, p=0.016. These results support the finding that collaboration between nurses, midwives, families and communities is needed to improve the psychological adjustment of postpartum mothers so that they have a strong desire to exclusively breastfeed their babies (Rahayu & Yunarsih, 2017). Support from health professionals, peers who are also breastfeeding, practical help and support from trusted people have been shown to meet mothers' emotional needs and overcome breastfeeding problems (Nanishi et al, 2021).…”
Section: Discussionsupporting
confidence: 72%
“…In this study, 50% of the respondents who received information on breastfeeding were shown to be successful in exclusive breastfeeding, p=0.016. These results support the finding that collaboration between nurses, midwives, families and communities is needed to improve the psychological adjustment of postpartum mothers so that they have a strong desire to exclusively breastfeed their babies (Rahayu & Yunarsih, 2017). Support from health professionals, peers who are also breastfeeding, practical help and support from trusted people have been shown to meet mothers' emotional needs and overcome breastfeeding problems (Nanishi et al, 2021).…”
Section: Discussionsupporting
confidence: 72%
“…It is consistent with studies conducted in; Motta town, Ethiopia 50.1% [ 14 ], Gahanna 64% [ 20 ], Debre Markos, Ethiopia 60.8% [ 29 ], Ecuador 62.8% [ 35 ] and Hawassa, Ethiopia 60.9% [ 16 ]. On the other hand, the result was higher than the studies done in; Indonesia 40% and 46% [ 36 , 37 ] Saudi Arabia 43.9% [ 38 ], Nigeria 33.5% [ 39 ], Papua New Guinea 17% [ 40 ], Democratic Republic Congo 39% [ 41 ], Addis Ababa, Ethiopia 29.3% [ 11 ] and North West Ethiopia 30.7% [ 12 ]. However, the result was lower than studies conducted in; Debre Birhan, Ethiopia 68.6% [ 17 ],Afar, Ethiopia 81.1% [ 19 ], Tigray, Ethiopia70.2% [ 18 ], United States73% [ 28 ] and India 87% [ 42 ].…”
Section: Discussionmentioning
confidence: 75%
“…Alianmoghaddam and colleagues used the theories of strength of weak ties and landscapes of care to explain importance of social relationships, social interactions and social support within virtual communities that are associated with breastfeeding [ 104 ]. Support systems for women were identified using the theory of maternal role attainment [ 105 ]. Social Franchise Model was used to design breastfeeding intervention—infant and young child feeding (IYCF) counselling services [ 91 ].…”
Section: Resultsmentioning
confidence: 99%
“…Whilst self-efficacy theories were used for intervention implementation and evaluation at individual levels [ 80 , 81 ], theories for systems intervention provided a larger context to examine effect of interventions on breastfeeding exclusivity [ 93 , 106 ]. Further, social theories provided opportunity to modify variables in the environment and test the influence of the modification on exclusive breastfeeding rates [ 91 , 105 ]. Thus, researchers may choose theories from these categories depending on the scope of their studies.…”
Section: Discussionmentioning
confidence: 99%